Contextualization of the Gospel in the Context of the Life of the Dani Tribe in Papua - Tony TEDJO; Tjutjun SETIAWAN; Ferry SIMANJUNTAK; Tomi YULIANTO; Kroliyus Puji SANYOTO (International Journal of Environmental, Sustainability, and Social Science, 2022)
Before the ascension of Jesus Christ into heaven, He gave the commandment, a Great Commission to preach the gospel to all nations. Dani tribe is one of the tribes in Papua and is certainly one of the objectives of the evangelistic mission. And it is not only Christianity that wants to reach out there but other religions as well. To carry out this mission, in this study the author formulated how the gospel could be understood and accepted by the Dani tribe. The authors used qualitative methods with a literature study approach. Each nation has a different culture and life from each other, even if the area is in the same country, When the Gospel will be preached in that area, the evangelists must study the context of the people's lives so that the gospel can be contextualized into the culture of life of the people. The authors hope it will benefit evangelists who will carry out missions on the Dani tribe through stone-burning ceremonies, work, and daily life.